Les intentions des Pères de la Confédération - Rémillard, Gil (Les Cahiers de droit)

(untitled) (Faculté de droit de l’Université Laval, 1979)
This paper attempts to elucidate the motives and purposes that gave rise to the constitutional compromise embodied in the BNA Act, 1867. In order to assess the ideological, political, economic and military considerations that shaped the outcome of the crucial Quebec conference of 1864, the author surveys earlier schemes for a federal union of British North America, examines the then current concept of federalism in the light of the American and Swiss precedents, discusses the political, economic and strategic factors supporting the idea of a Canadian federation, and finally gives an account of the manner in which the Quebec and London conferences achieved a practical balance between the diverging views of their participants. This recreation of historical conditions surrounding the birth of Confederation sets the present constitution of Canada in the light of an essentially pragmatic answer to the difficulties and needs of its times. While this compromise called for a strong central authority, it was also based on a strongly-felt need for provincial autonomy.